2017
DOI: 10.12955/cbup.v5.1059
|View full text |Cite
|
Sign up to set email alerts
|

Laser Stokes-Polarimetry of the Erythrocytes Suspension at Comorbid Course of Coronary Artery Disease, Diabetes Mellitus Type 2 and Anemia

Abstract: Abstract:Introduction: Investigation of the rheological properties of the erythrocytes is one of the crucial issues in the pathogenesis of most diseases of internal organs. Changes in the morphological structure of the red blood cell membrane serve as an early diagnostic criterion of coronary artery disease, diabetes mellitus type 2 and anaemia, thus a search for modern methods of investigation which can be used for early detection of erythrocytes membrane disorders is of great importance. Methods of laser pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Kunnen et al [8] employed the Stokes polarimetric imaging with circularly polarized light to differentiate the cancerous tissue and noncancerous tissue by mapping the Stokes vector of backscattered light on the Poincaré sphere. Nataliia Pavlyukovich et al [9] demonstrated Stokes polarimetric imaging could be used for early detection of erythrocytes membrane disorders, which was meaningful for the diagnosis and treatment of most diseases of internal organs such as coronary artery disease and type 2 diabetes. Mazumder et al [10] used Stokes polarimetry to investigate the molecular structure of second harmonic generation active molecules such as collagen type I and myosin, which means Stokes polarimetry has great potential in the field of molecular structure in biomedicine.…”
Section: Introductionmentioning
confidence: 99%
“…Kunnen et al [8] employed the Stokes polarimetric imaging with circularly polarized light to differentiate the cancerous tissue and noncancerous tissue by mapping the Stokes vector of backscattered light on the Poincaré sphere. Nataliia Pavlyukovich et al [9] demonstrated Stokes polarimetric imaging could be used for early detection of erythrocytes membrane disorders, which was meaningful for the diagnosis and treatment of most diseases of internal organs such as coronary artery disease and type 2 diabetes. Mazumder et al [10] used Stokes polarimetry to investigate the molecular structure of second harmonic generation active molecules such as collagen type I and myosin, which means Stokes polarimetry has great potential in the field of molecular structure in biomedicine.…”
Section: Introductionmentioning
confidence: 99%